SUPPLY CHAIN ANALYSIS OF COPRA IN PAKUURE VILLAGE TENGA OF SOUTH MINAHASA - Karenia Keintjem; Joy E. Tulung; Fitty V. Arie (Universitas Sam Ratulangi, 2023)
Abstract: North Sulawesi is known as one of the places that produce Copra the most in Indonesia. In North Sulawesi, the agriculture sector is considered as one of the superior commodities for the economy. The people of North Sulawesi have been cultivating coconut to be processed into copra as one of their main sources of income. The plantation in Pakuure Village, Tenga sub-district, South Minahasa Regency is an area that is overgrown with coconut plants. This village it is one of the producers of coconut plants in North Sulawesi. Based on the interview conducted with all of the ten informants which are the copra buyers, and then the result shows all of them are the copra buyers, and most informants almost have the same answers about being a copra buyer as the main commodity. It is also discovered that each of the ten informants have their own different experiences and opinions as a copra buyer and how the supply chain can affect their income. The quality of copra determines the price of copra, thus affects their income. According to them the quality of copra determines the price of the copra. Good quality copra always gets the best price, while the bad quality ones tend to have the worst price, that of course affects their income as a copra buyer that the supply chain of copra definitely affects the income of the copra buyers, as most of them being a copra buyer as their main source of income. From the results of the interview with all informants, researcher found that the supply chain of copra definitely affects the income of the copra buyers, as most of them being a copra buyer as their main source of income. Especially when it comes to quality control, if the copra farmers came up with a huge amount bad quality copra, it can heavily affect the final outcome of the copra buyers. Keywords: supply chain